TOPORS, a Dual E3 Ubiquitin and Sumo1 Ligase, Interacts with 26 S Protease Regulatory Subunit 4, Encoded by the PSMC1 Gene - Czub, Barbara (PLoS One, 2016)
The significance of the ubiquitin-proteasome system (UPS) for protein degradation has been highlighted in the context of neurodegenerative diseases, including retinal dystrophies. TOPORS, a dual E3 ubiquitin and SUMO1 ligase, forms a component of the UPS and selected substrates for its enzymatic activities, such as DJ-1/PARK7 and APOBEC2, are important for neuronal as well as retinal homeostasis, respectively. TOPORS is ubiquitously expressed, yet its mutations are only known to result in autosomal dominant retinitis pigmentosa. We performed a yeast two-hybrid (Y2H) screen of a human retinal cDNA library in order to identify interacting protein partners of TOPORS from the retina, and thus begin delineating the putative disease mechanism(s) associated with the retina-specific phenotype resulting from mutations in TOPORS. The screen led to isolation of the 26 S protease regulatory subunit 4 (P26s4/ PSMC1), an ATPase indispensable for correct functioning of UPS-mediated proteostasis. The interaction between endogenous TOPORS and P26s4 proteins was validated by co-immuno-precipitation from mammalian cell extracts and further characterised by immunofluorescent co-localisation studies in cell lines and retinal sections. Findings from hTERT-RPE1 and 661W cells demonstrated that TOPORS and P26s4 co-localise at the centrosome in cultured cells. Immunofluorescent staining of mouse retinae revealed a strong P26s4 reactivity at the interface between retinal pigmented epithelium (RPE) layer and the photoreceptors outer segments (OS). This finding leads us to speculate that P26s4, along with TOPORS, may have a role(s) in RPE phagocytosis, in addition to contributing to the overall photoreceptor and retinal homeostasis via the UPS.